Peripheral Nerve Injuries: A Clinical Guide - Birch, Rolfe; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Peripheral Nerve Injuries: A Clinical Guide is a fully illustrated and informative reference on injuries within the peripheral nervous system. It incorporates new knowledge in molecular and cellular events which underlie the response of nerves to injury, regeneration and neuropathic pain. Written by a leading expert in the field, Peripheral Nerve Injuries: A Clinical Guide, is a valuable resource for surgeons in residence and training.
The Peripheral Nervous System: Anatomy and Function -- Reactions to Injury -- Regeneration and Recovery of Function -- Clinical Aspects of Nerve Injury -- Operating on Peripheral Nerves.
Keywords: Medicine; Neurology; Surgery; Trauma; Medicine & Public Health; Surgery; Neurology; Traumatic Surgery